Evaluation of an Annual Campus Newspaper Insert at Michigan State University - Michael V. Doyle; Daniel T. Davis (Journal of Applied Communications, 1985)
In early 1984, Maxine Ferris, head of the Agriculture information Service at Michigan State University, began making plans to conduct research concerning the overall communication effectiveness of the College of Agriculture and Natural Resources (ANR) annual insert in The MSU News Bulletin, a tabloid newspaper published weekly and circulated among the University's faculty and staff.